Formulation of Criminal Law System Policy in the Settlement of Compensation for Corruption Crimes (International Forum of Researchers and Lecturers, 2025)
Corruption in Indonesia is not merely a moral transgression but an extraordinary economic crime that depletes national resources. The ultimate objective of corruption eradication, therefore, must be the restoration of state financial losses (asset recovery). However, the current formulation of the criminal law system specifically Article 18 of Law No. 31 of 1999 contains a critical policy flaw. The provision of